2020
DOI: 10.1371/journal.pntd.0008080
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic and parasitological parameters are modulated in EBi3-/- mice infected with Schistosoma mansoni

Abstract: Schistosoma mansoni adaptive success is related to regulation of replication, transcription and translation inside and outside the intermediate and definitive host. We hypothesize that S. mansoni alters its epigenetic state in response to the mammalian host immune system, reprogramming gene expression and altering the number of eggs. In response, a change in the DNA methylation profile of hepatocytes could occurs, modulating the extent of hepatic granuloma. To investigate this hypothesis, we used the EBi3 -/mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
4
4
0
Order By: Relevance
“…However, taken in the context of our recent findings that ES-62 can promote both health- and life-span in male mice undergoing obesity-accelerated ageing 6 , it is in line with helminths having evolved such an overarching inflammation-resolving and repair/regeneration strategy to counter the chronic inflammation and tissue pathology they would otherwise elicit. Consistent with this, it has recently been reported that another parasitic trematode, Schistosoma mansoni, induces hepatocyte DNA hypomethylation that is associated with reduced tissue pathology and granuloma formation in the acute phase of infection in mice 101 , supporting the idea that epigenetic changes induced by helminth infection appear to be indirectly important in promoting long-term helminth survival.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…However, taken in the context of our recent findings that ES-62 can promote both health- and life-span in male mice undergoing obesity-accelerated ageing 6 , it is in line with helminths having evolved such an overarching inflammation-resolving and repair/regeneration strategy to counter the chronic inflammation and tissue pathology they would otherwise elicit. Consistent with this, it has recently been reported that another parasitic trematode, Schistosoma mansoni, induces hepatocyte DNA hypomethylation that is associated with reduced tissue pathology and granuloma formation in the acute phase of infection in mice 101 , supporting the idea that epigenetic changes induced by helminth infection appear to be indirectly important in promoting long-term helminth survival.…”
Section: Discussionsupporting
confidence: 69%
“…Interestingly, such epigenetic remodelling was impacted by the inflammatory context, which modulated the (reciprocal) epigenetic changes occurring in both the host hepatocytes and the worms to determine the levels of liver pathology 101 . The potential importance of the evolution of such complex host-worm epigenetic regulatory networks is highlighted by evidence that CD4 T cells, from children recently exposed to tuberculosis and infected with Schistosoma haematobium showed profound differential DNA methylation, relative to those from uninfected children, that was associated with Th2-skewing of tuberculosis (TB)-specific responses away from the protective Th1/IFN γ phenotype 102 .…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic markers are produced through interactions between the parasite and the environment, as well as by interactions with host-specific immune responses. Therefore, to use epigenetic factors as biomarkers, the relationships between parasite and its definitive host must be considered ( Mota et al, 2020 ). In epigenetic processes where the interactions occur by modifying the epigenetic state, there is the participation of enzymes such as: DNA methyltransferases (DNMT), protein arginine methytransferase (PRMT), protein lysine methyltransferase (PKMT), lysine demethylases (KDM), protein lysine acetyltransferase, protein lysine deacetylase (HDAC), kinases, ubiquitin conjugating enzymes (E2), deubiquitinating enzymes (DUBs), and others, presented in Table 1 .…”
Section: Molecular Epigenetic Markers Associated To Schistomentioning
confidence: 99%
“…In S. haematobium for example the promoter of RASSF 1A and TIMP3 genes is hypermethylated and can be used as a biomarker of S. haematobium infection ( Zhong et al, 2013 ). Disturbance in the global content of 5-mC and in the expression of DNMTs and TETs (Ten eleven translocation) were detected in the liver of infected mice compared to uninfected maybe in the future some specific region or a set of expression profile could be used as schistosomiasis biomarker ( Mota et al, 2020 ).…”
Section: Potential Classes Of Epigenetic Biomarkers Applied To Schistmentioning
confidence: 99%
See 1 more Smart Citation